Correlation between the occlusal vertical dimension and the pupil rima oris distance among Sundanese population - Akhma, Nur Emalina; Sumarsongko, Taufik; Rikmasari, Rasmi (Padjadjaran Journal of Dentistry, 2017)
Introduction: Among the most complex restorative challenges for a dentist is that related to determine the occlusal vertical dimension (OVD). Objective methods of determining the OVD offers significant advantages because no radiographs or other special measuring devices are required. Previous review said that the OVD is similar to the pupil-rima oris distance among the population of India. The purpose of this study was to compare whether there was differences between the OVD and the pupil-rima oris distance among Sundanese population. Method: This study was an analytical cross sectional approach. A total of fifty Sundanese students of Faculty of Dentistry, Universitas Padjadjaran who have fulfilled all criteria were chosen randomly to be measured the OVD and the pupil-rima oris distance. Result: Results showed that there was no significant difference between the OVD and the pupil-rima oris distance (α=5%). There were strong correlations between the OVD and the pupil-rima oris distance (p<0.05). An analysed with Spearman’s rank correlation statistic (α=5%) reveals that there was a significant difference between males and females in the OVD and the pupil-rima oris distance. Conclusion: Based on the analysed data, we can conclude that there wass no significant difference between the OVD and the pupil-rima oris distance, thus, the pupil-rima oris distance can be suggested as an objective method to determine the length of OVD in Sundanese population.